Chiral liquid-crystalline polyacrylates from (S)-(-)-2-methyl-1-butanol. Synthesis, mesomorphic properties and light scattering - Merlo Aloir A. (Journal of the Brazilian Chemical Society, 2001)
The synthesis and mesomorphic behavior of two chiral side chain liquid crystalline polyacrylates from (S)-(-)-2-methyl-1-butanol are described. These new polyacrylates show a dependence of the phase transition temperatures on both, molecular weight and spacer length. The polyacrylate with four methylene units in the spacer exhibits a chiral nematic phase whereas the polyacrylate with a spacer containing eleven methylene units presents a smectic phase. In addition, the chiral nematic phase appears for low molecular weight and smectic phase for high molecular weight polyacrylates. Light scattering experiments were performed in dilute solutions of the polyacrylate containing eleven methylene units in tetrahydrofuran and dichloromethane. Values for weight averaged molecular weight, radius of gyration and second virial coefficient were determined by static light scattering whereas the diffusion coefficient and the hydrodynamic radius of the chains were obtained by photon correlation spectroscopy. A comparison between both techniques indicates that the chain behavior can be taken as typical for a polydisperse linear chain in a good solvent.